2023
DOI: 10.1186/s10194-023-01581-6
|View full text |Cite
|
Sign up to set email alerts
|

Brain structure and cortical activity changes of new daily persistent headache: multimodal evidence from MEG/sMRI

Abstract: Background New daily persistent headache (NDPH) is a rare but debilitating primary headache disorder that poses a significant burden on individuals and society. Despite its clinical importance, the underlying pathophysiological mechanisms of NDPH remain unclear. In this study, we aimed to investigate the brain structural changes and neural activity patterns in patients with NDPH using multimodal brain imaging analysis of structural magnetic resonance imaging (sMRI) combined with magnetoencephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Interestingly, a 2023 study used structural MRI to distinguish between adolescents with long COVID headache and those with primary headache disorders, including NDPH, revealing potential biomarkers for conditions that, so far, have only clinical criteria [ 32 ]. While a 2022 adult study did not show any gray matter differences in NDPH compared to healthy controls [ 33 ], a 2023 study investigating patients aged 14–70 showed changes in brain morphology such as cortical surface area, cortical thickness, and GM volume, accompanied by abnormal cortical neural activity [ 34 ]. A 2023 brain mapping study in adults showed abnormal functional connectivity in multiple brain regions involved in the perception and regulation of emotion and pain [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a 2023 study used structural MRI to distinguish between adolescents with long COVID headache and those with primary headache disorders, including NDPH, revealing potential biomarkers for conditions that, so far, have only clinical criteria [ 32 ]. While a 2022 adult study did not show any gray matter differences in NDPH compared to healthy controls [ 33 ], a 2023 study investigating patients aged 14–70 showed changes in brain morphology such as cortical surface area, cortical thickness, and GM volume, accompanied by abnormal cortical neural activity [ 34 ]. A 2023 brain mapping study in adults showed abnormal functional connectivity in multiple brain regions involved in the perception and regulation of emotion and pain [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Within the CDH population at tertiary centers, the prevalence of NDPH in children and adolescents ranges from 0.9 to 35%, compared to 1.7 to 10.8% in adults [19]. It maintains a female predominance throughout life, with a 2.5:1 female/male ratio in adults and a 1.8:1 female/male ratio in children and adolescents, and has an earlier age at onset in females (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) than in males (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) [2].…”
Section: Epidemiologymentioning
confidence: 99%
“…Research has analyzed a subtype of headache within this category known as new daily persistent headache (NDPH) ( Robbins et al, 2010 ), characterized by the sudden onset of daily headaches lasting for 3 months or longer, with secondary causes excluded. A study ( Qiu et al, 2023 ) using structural magnetic resonance imaging combined with multimodal brain imaging analysis of magnetoencephalography found that NDPH patients had abnormal brain morphology such as cortical area, cortical thickness, and gray matter volume, accompanied by abnormal cortical neural activity. Another study ( Wang et al, 2023 ) using fMRI to map abnormal FC in NDPH patients showed abnormal FC in multiple brain regions involved in emotion and pain perception and regulation, but these abnormalities did not correlate with clinical features.…”
Section: The Role Of Fmri Technology In Diagnosing Primary Headachesmentioning
confidence: 99%
“…6 Our previous studies showed that adult patients with NDPH have unique alterations in hemodynamics, regional homogeneity, multiple frequency amplitudes of low-frequency fluctuation, cortical activity, and brain functional connectivity (FC) in certain brain regions. [7][8][9][10] FC is defined as the temporal coincidence of spatially distant neurophysiological events. Over the last decade, an increasing number of studies have applied magnetic resonance imaging (MRI) to explore FC in headache disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggested that there were abnormalities in brain function and structure in adolescents with NDPH 6 . Our previous studies showed that adult patients with NDPH have unique alterations in hemodynamics, regional homogeneity, multiple frequency amplitudes of low‐frequency fluctuation, cortical activity, and brain functional connectivity (FC) in certain brain regions 7–10 . FC is defined as the temporal coincidence of spatially distant neurophysiological events.…”
Section: Introductionmentioning
confidence: 99%